Adenosine deaminase activity in rheumatoid pleural effusion. Issue 5 (May 1988) - Ocaña, I; Ribera, E; Martinez-Vázquez, J M; Ruiz, I; Bejarano, E; Pigrau, C; Pahissa, A
Abstract : The activity of adenosine deaminase was studied in nine cases of rheumatoid pleural effusion, showing an increase in enzyme activity in all. Rheumatoid arthritis seems unique, however, as it cannot be differentiated from pleural tuberculosis on the basis of this test. Selective increase of adenosine deaminase in both conditions is attributed to stimulation of T lymphocytes in the pleural fluid.